Diseases of women and children in the city of Constantine in the light of the death record (1840-1841) - boucheribcha, Hayat; belalia, Miloud (The Algerian Historical Journal, 2026)
We aim through this research paper to identify the most important diseases that affected women and children, in the city of Constantine in the year (1841-1840) based on the death record, which monitored data and information about the health situation, and documented the most important diseases, which spread in the city at the beginning of the French occupation. We have tried to focus on the group most vulnerable to diseases, the segment of women and children, which was suffering from deprivation and marginalization, by researching the nature of these diseases that cause death, and the causes of their spread linked to climatic factors, or living conditions; Such as malnutrition, lack of hygiene, and lack of attention to the health aspect during that period.